Significance of Reporting Cannon Balls in Diagnosing Bacterial Vaginosis Infection in PAP Smear (Nepal Medical College Journal, 2021)
Bacterial vaginosis is the most common cause of vaginitis. It is caused by depopulation of lactobacilli from the normal vaginal flora and overgrowth of Gardnerella vaginalis and other anaerobic species. Pap smear being a screening and diagnostic tool for malignancy, is equally important to diagnose infective pathology as well. This study tried to establish the significance of reporting the presence of cannon balls in Pap smears and whether their presence suggested bacterial vaginosis or not. This was a cross sectional study conducted at Nepal Medical College, Teaching Hospital (NMCTH), Kathmandu for duration of one year (January 2020 to December 2020). Pap smears were sent from gynaecology department and standard routine Pap stain was done in Pathology Department. Presence of bacterial vaginosis and cannon balls were noted. Total of 799 Pap smears were received. The mean age of bacterial vaginosis was 38.2 ± 9.6 years. The age group of 31-40 years (n=32, 39%) was most commonly affected. Bacterial vaginosis was seen in 81 pap smears out of 799 pap smears. The prevalence of bacterial vaginosis was 10.1%. Of the total of 799 cases of Pap smears, cannon balls were seen in 9.1% cases and among the bacterial vaginosis, cannon balls were seen in 48% cases. There was significant association between cannonballs and bacterial vaginosis (p < 0.0001). Thus, the present study re-enforces the fact that Pap smear is also very effective tool to diagnose bacterial vaginosis.